Stimulant Adoption of Mobile Game Services in Indonesia - Acai Sudirman; Darwin Lie; Nana Triapnita Nainggolan; Sherly Sherly; Martin Yehezkiel Sianipar (International Journal of Entrepreneurship and Sustainability Studies, 2022)
The rapid development of information technology corresponds to the development of humans who increasingly need technology to facilitate their business. Currently, in addition to business development, the development of mobile games has also experienced a significant increase in terms of the number of users. The increasingly rapid development of game enthusiasts has an impact on the behavior of generation Z and the millennial generation in choosing the quality of the games they want. The main objective of this research is to analyze the determinants of mobile game adoption among Generation Z and Millennials. The study tool was an online survey that was given to 210 participants, all of whom were Millennial and Generation Z players of mobile game services. The researchers then put the theory to the test by utilizing the Partial Least Square (PLS) type of structural equation modeling (SEM) and the SmartPLS version 3.0 program to examine it. The study's findings demonstrate that perceived enjoyment, perceived ease of use, and habit have a significant and positive impact on usage intention. The managerial implications of this research conclude that one of the biggest effects of playing games service is to make people happy. Of course they feel happy because when they play games, they don't feel the pressures of life. As if they are in another world that makes them the main character.